Mapping of MN1 Sequences Necessary for Myeloid Transformation - Kandilci, Ayten; Surtel, Jacqueline; Janke, Laura J.; Neale, Geoffrey; Terranova, Sabrina; Grosveld, Gerard C. (My University, 2013)
The MN1 oncogene is deregulated in human acute myeloid leukemia and its overexpression induces proliferation and represses myeloid differentiation of primitive human and mouse hematopoietic cells, leading to myeloid leukemia in mouse models. To delineate the sequences within MN1 necessary for MN1-induced leukemia, we tested the transforming capacity of in-frame deletion mutants, using retroviral transduction of mouse bone marrow. We found that integrity of the regions between amino acids 12 to 458 and 1119 to 1273 are required for MN1's in vivo transforming activity, generating myeloid leukemia with some mutants also producing T-cell lympho-leukemia and megakaryocytic leukemia. Although both full length MN1 and a mutant that lacks the residues between 12-228 (?12-228 mutant) repressed myeloid differentiation and increased myeloproliferative activity in vitro, the mutant lost its transforming activity in vivo. Both MN1 and ?12-228 increased the frequency of common myeloid progentiors (CMP) in vitro and microarray comparisons of purified MN1-CMP and ?12-228-CMP cells showed many differentially expressed genes including Hoxa9, Meis1, Myb, Runx2, Cebpa, Cebpb and Cebpd. This collection of immediate MN1-responsive candidate genes distinguishes the leukemic activity from the in vitro myeloproliferative capacity of this oncoprotein. © 2013 Kandilci et al. © 2013 Elsevier B.V., All rights reserved.
Keywords: CCAAT enhancer binding protein alpha; CCAAT enhancer binding protein beta; CCAAT enhancer binding protein delta; protein Myb; transcription factor HoxA9; transcription factor RUNX2; Mn1 protein, mouse; oncoprotein; tumor protein; animal cell; animal tissue; antibody detection; article; biotinylation; bone marrow cell; carcinogenesis; cell differentiation; cell lineage; cell proliferation; cell renewal; controlled study; gene expression; gene expression profiling; gene mapping; gene sequence; genetic transcription; genetic transformation; in vitro study; microarray analysis; MN1 gene; mouse; myeloproliferative disorder; nonhuman; oncogene; open reading frame; protein purification; signal transduction; acute granulocytic leukemia; amino acid sequence; animal; cancer stem cell; cell count; cell transformation; gene deletion; gene expression regulation; gene vector; genetic transduction; genetics; human; metabolism; molecular genetics; mortality; pathology; Retrovirus; survival; Amino Acid Sequence; Animals; Bone Marrow Cells; Cell Count; Cell Differentiation; Cell Proliferation; Cell Transformation, Neoplastic; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Genetic Vectors; Humans; Leukemia, Myeloid, Acute; Mice; Molecular Sequence Data; Myeloid Cells; Neoplasm Proteins; Neoplastic Stem Cells; Oncogene Proteins; Retroviridae; Sequence Deletion; Survival Analysis; Transduction, Genetic